Metformin-associated gut microbiota remodeling correlates with reinvigorated splenic immunity in aged mice: microbiome-immune crosstalk via the gut-spleen axis - Ding, Shu-Qin; Lyu, Xin-Yi; Zhou, Shi-Yu; Fang, Yi-Wan; Ji, Hao-Xin; Li, Jiang-Yan; Lü, He-Zuo (Frontiers in Immunology, 2025)
Background and aimImmunosenescence involves age-related immune decline and chronic inflammation, with the spleen serving as a critical hub for immune dysregulation. While gut microbiota influences systemic immunity, its specific role and the potential existence of a gut-spleen axis in mediating splenic aging remains unclear. Therefore, we investigated whether metformin, a microbiota-modulating geroprotective drug, alleviates splenic immunosenescence in aged mice, specifically exploring the link between gut microbiota remodeling and splenic immune rejuvenation.MethodsAged C57BL/6 mice (15-month-old) received oral metformin (300 mg/kg/day) or vehicle for 5 months. Systemic toxicity and metabolism were monitored. Splenic immune subsets were analyzed using flow cytometry and immunohistochemistry. Gut microbiota composition (16S rRNA sequencing), cytokine levels (RT-qPCR), and functional pathways were assessed.ResultsMetformin caused no hepatorenal toxicity or weight changes. Treated mice exhibited increased cytotoxic T cells (Tc) and macrophages in the spleen, with reduced Th/Tc ratios and M1/M2 polarization. Pro-inflammatory cytokines (Ifng, Il17a, Il1b, Il6) decreased, while anti-inflammatory markers (Arg1, Tgfb1) rose. Gut microbiota showed enriched Akkermansia, Muribaculum, and Duncaniella, but reduced Lactobacillus. Akkermansia/Muribaculum negatively correlated with pro-inflammatory cytokines, whereas Lactobacillus and Lachnospiraceae linked to pro-inflammatory responses. Functional prediction analysis based on 16S rRNA sequencing data indicated upregulation of bile acid metabolism and oxidative phosphorylation pathways.ConclusionMetformin reshapes the gut microbiota, which is associated with mitigation of age-associated splenic immune dysregulation, favoring anti-inflammatory macrophage polarization and cytotoxic T cell expansion. Critically, our findings establish the gut-spleen axis as a key mediator of splenic immunosenescence and a novel therapeutic target, which positions metformin as a promising microbiota-directed geroprotective agent. Future research should prioritize mechanistic dissection of gut-spleen communication and clinical validation of metformin’s geroprotective efficacy in human populations.